The Development of a Competency Assessment Standard for General Practitioners in China - Xin Rao; Xin Rao; Jinming Lai; Hua Wu; Yang Li; Xingzhi Xu; Xingzhi Xu; Colette Joy Browning; Colette Joy Browning; Colette Joy Browning; Colette Joy Browning; Shane Andrew Thomas; et al. (Frontiers Media S.A., 2020)
This paper describes the development of a competency assessment standard for General Practitioners in Shenzhen, China. The standard is to be used for developing and delivering the training curriculum for General Practitioners and to enable rigorous assessment of the mastery of the standards by GP trainees. The requirement for the training of General Practitioners in China is mandated by government policy requires an international standard curriculum to meet the needs of patients and the community. A modified Delphi process was employed to arrive at a curriculum consensus. An expert panel and 14 expert working groups derived from the expert panel were established to review and evaluate national and international competency standards for General Practice and develop a set of standards, through a modified Delphi methodology. Forty three experts were involved in the project. The project resulted in a detailed curriculum statement. The curriculum was then used in 2017 and 2018 where pilot examinations of GP trainees (n = 298 and n = 315, respectively) were conducted to assess the trainee's competencies against the Standards. The examination included two modules, a written test (Module A) and a practical test (Module B). The success rate for participants was relatively low with the majority not successfully completing the assessments. The assessments will be further refined in subsequent work. The project achieved its goal of developing a rigorously evaluated standard to support clinical practice and the training and assessment of GPs.